National Examination in SMPN 2 Palopo: A Case Study on Students’ Readiness in English Test - Faradiba Ade Iswara Jaya; Amalia Yahya; Jufriadi Jufriadi (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2020)
The research aims to investigate whether Students’ Readiness toward National Examination (A Case Study in SMPN 2 Palopo). The problem statement of the research was, “How are their readiness in facing national examination”? This research used the Descriptive Quantitative Method. The population of this research was 167 students from the ninth grade students of Junior High School Number 2 Palopo. The total numbers of the students are ten students. The researcher took five students from each class as the sample. The sample was selected using a purposive sampling technique. The researcher used this technique based on their consideration. The result of the analysis can explain that the researcher analyzed the result to measure the students’ readiness in facing national examination. The researcher has conducted the result of the test showed their readiness to face the national examination. The result categorized into average classification. The highest score is 74, the middle score is 66, the lowest score is 60, and the mean score is 67.